MOTIVASI INDONESIA MELAKUKAN KERJA SAMA DENGAN TIONGKOK DALAM KONSERVASI PANDA RAKSASA (GIANT PANDA) - Halim, Fifi Melyna; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The giant panda (Ailuropoda melanoleuca) is a protected wildlife species endemic to China. In 2017, a pair of giant pandas, Hu Chun and Cai Tao, were brought to Indonesia from China. The same year, a giant panda conservation cooperation project was launched. This marked a significant milestone in the friendly relationship between the two countries. As a partner country in the giant panda conservation cooperation project initiated by China, Indonesia also considered factors that ultimately motivated the project. This study employs a qualitative method using, primary and secondary data obtained from books, academic journals, Indonesian and Chinese government publications, and Taman Safari Indonesia publications. The research adopts a constructivist perspective, with the theory of Foreign Policy Analysis and a Foreign Policy Decision-Making approach. Indonesia's motivation for collaborating on giant panda conservation is to strengthen cooperation in wildlife conservation and other areas, particularly economics, investment, and infrastructure, as well as to strengthen its friendly relations with China. As diplomatic relations with China have long been established since 1950, maintaining good relations between the two countries is no simple matter. Therefore, various efforts, such as cooperation in various fields, are being strengthened. Keywords: Cooperation, Conservation, Giant Panda, Motivation, Indonesia, China.